Health, nutrition and exercise - Bogueva, Diana; Marinova, Dora (Emerald, 2024)
Many in Generation Z are concerned about health, nutrition, and lifestyle. They are sensitive to the social determinants of health, represented through concerns about access to health care, viable and affordable housing, poverty, and unemployment. They are also concerned about food choices, their environmental footprint, and the way food is produced. There is similarly high awareness about the importance of nutrition for health. Despite engaging in physical exercise, Generation Z is also exposed to the risks associated with obesity and sedentary lifestyle.